Is the combination of corticosteroids plus NSAIDs improve the preemptive analgesia after third molars surgery? A systematic review and meta-analysis (Research, Society and Development, 2020)
This study aimed to perform a systematic review and meta-analysis to evaluate the preemptive action of the combination of corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs) or both drugs singly after third molars surgery. It was performed a search on the PubMed/MEDLINE, Scopus, and Cochrane databases, according to the PRISMA criteria, with no time restrictions up to March 2020. The postoperative pain was evaluated, qualitatively, through the visual analogue scale (VAS) and the number of rescue analgesics (NRA). The edema and trismus were evaluated in a qualitative way through linear measures. Besides that, a meta-analysis of the post-operative pain (VAS) was performed. It was found 103 articles, which four articles were selected according to the inclusion and exclusion criteria. A total of 208 patients was evaluated and the combination of corticosteroids and NSAIDs showed great behavior in the preemptive action after third molars surgery for all the parameters evaluated when compared to both drugs singly. Meta-analysis about the VAS showed that the combination of drugs reduced significantly the postoperative pain when compared to the NSAIDs singly (P